1996
DOI: 10.1177/107602969600200105
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Versus Preoperative Initiation of Deep-Vein Thrombosis Prophylaxis with a Low-Molecular-Weight Heparin (Nadroparin) in Elective Hip Replacement

Abstract: The aim of this multicenter, randomized, double-blind study performed in patients undergoing elective hip surgery was to compare the efficacy and safety of prophylaxis with low-molecular-weight heparin (LMWH) (Nadroparin, 7,500 anti-Xa IC units for the first 3 days and 10,000 from the fourth day on, s.c. o.i.d.) begun in one group shortly after surgery and in the other 12 h before operation, as is usually recommended. Preoperative administration (drug or placebo) was the only difference between the two groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The two reviews yielded to discordant results, as Kearon and Hirsh failed to show a difference in efficacy between preoperative and postoperative-initiated LMWH prophylaxis for THR patients, 35 whereas Hull et al concluded that preoperative initiated LMWH was significantly more effective when compared with postoperative-initiated LMWH. 36 Three studies have directly compared preand postoperative commencement of LMWH prophylaxis, the first two in patients undergoing elective hip surgery, 16,37 and the last one in patients undergoing surgery for hip fracture. 38 As shown in Table 7, the first study did not show appreciable differences between the two strategies, 37 the second showed a higher risk of major bleeding in case of a early initiation, 16 and the third study (although conducted in fewer patients) showed an impressive superiority of the preoperative initiation in case of hip fracture.…”
Section: When Should One Start Thromboprophylaxis?mentioning
confidence: 99%
See 1 more Smart Citation
“…The two reviews yielded to discordant results, as Kearon and Hirsh failed to show a difference in efficacy between preoperative and postoperative-initiated LMWH prophylaxis for THR patients, 35 whereas Hull et al concluded that preoperative initiated LMWH was significantly more effective when compared with postoperative-initiated LMWH. 36 Three studies have directly compared preand postoperative commencement of LMWH prophylaxis, the first two in patients undergoing elective hip surgery, 16,37 and the last one in patients undergoing surgery for hip fracture. 38 As shown in Table 7, the first study did not show appreciable differences between the two strategies, 37 the second showed a higher risk of major bleeding in case of a early initiation, 16 and the third study (although conducted in fewer patients) showed an impressive superiority of the preoperative initiation in case of hip fracture.…”
Section: When Should One Start Thromboprophylaxis?mentioning
confidence: 99%
“…36 Three studies have directly compared preand postoperative commencement of LMWH prophylaxis, the first two in patients undergoing elective hip surgery, 16,37 and the last one in patients undergoing surgery for hip fracture. 38 As shown in Table 7, the first study did not show appreciable differences between the two strategies, 37 the second showed a higher risk of major bleeding in case of a early initiation, 16 and the third study (although conducted in fewer patients) showed an impressive superiority of the preoperative initiation in case of hip fracture. 38 The comparability between these studies is problematic because of different study designs, patient population, and drug utilized.…”
Section: When Should One Start Thromboprophylaxis?mentioning
confidence: 99%
“…The two reviews yielded discordant results, as Kearon and Hirsh failed to show a difference in efficacy between preoperative and postoperativeinitiated LMWH prophylaxis for THR patients (84), whereas Hull et al concluded that pre-operative initiated LMWH was significantly more effective when compared with postoperative-initiated LMWH (85). Three studies have directly compared pre-and postoperative start of LMWH prophylaxis, the first two in patients undergoing elective hip surgery (82,86), and the third in patients undergoing surgery for hip fracture (87). The first study did not show appreciable differences between the two strategies (86), the second showed a higher risk of major bleeding with early initiation (82), and the third (although conducted in fewer patients) showed an impressive superiority of the preoperative initiation in patients with hip fracture (87) ( Table 11).…”
Section: Major Orthopedic Surgerymentioning
confidence: 99%
“…Three studies have directly compared pre-and postoperative start of LMWH prophylaxis, the first two in patients undergoing elective hip surgery (82,86), and the third in patients undergoing surgery for hip fracture (87). The first study did not show appreciable differences between the two strategies (86), the second showed a higher risk of major bleeding with early initiation (82), and the third (although conducted in fewer patients) showed an impressive superiority of the preoperative initiation in patients with hip fracture (87) ( Table 11). As the comparabil-ity between these studies is problematic due to different study designs, patient population and drug utilized, the problem remains open.…”
Section: Major Orthopedic Surgerymentioning
confidence: 99%
“…Consequently, chemoprophylaxis timing is frequently based on personal experience and surgical dogma, leading to significant and often irrational variability in practice 5. Notably, evidence in other fields, such as orthopedic surgery, suggests that preoperative initiation of chemoprophylaxis confers no additional benefit for reducing VTE risk compared with postoperative 6. In addition, in several general surgery cohorts, initiation before skin closure increased the risk of postoperative bleeding 7.…”
mentioning
confidence: 99%